MISI DI ZAMAN KITA MENURUT SURAT-SURAT BENEDIKTUS XVI PADA HARI MISI SEDUNIA 2006-2011 - Floribertus Hasto Rosariyanto (P3TK, Sanata Dharma University, 2012)
At the time of the Council, almost everyone recognized that the churchs MISIonary activity was facing an identity crisis. New attitudes were raising new questions. Fifty years afterwards the Church cannot pretend of having been able to overcome them. The letters of Pope Benedict XVI showed that new questions seem never end. Demographical shift of Christianity, the spread of violence, individualism, secular culture are only some indications of the new realities which the Catholic Church has to address. In those uneasy situations, the Pope reminds the faithful not to lose hope. He encourage them to build a new culture, that is, solidarit ; and invite all people around the globe to create a peaceful atmosphere and to make the world as a home for everyone.